Metabolite fingerprinting of Urospatha sagittifolia (Araceae) tubers at different growth stages by multi-platform metabolomics and molecular networking - Pastuña Fasso, Jefferson Vladimir (2024)
Urospatha sagittifolia is a medicinal plant with antivenom, antihemorrhagic and anti-inflammatory properties commonly used by vulnerable Amazon indigenous communities to tackle venomous snakebites and their life-threatening consequences. Despite its pharmacological potential as a rich source of drug candidates, its metabolomic profile remains unknown. In this context, this study integrated mass spectrometry-based metabolomics, multivariate analysis, and molecular networks to uncover the chemical composition of U. sagittifolia and its dynamic metabolic changes during three plant growth stages (seedling, juvenile and adult). In general, 50 metabolites were identified in U. sagittifolia tubers by LC-MS (43 metabolites) and GC-MS (seven metabolites). Multivariate analysis using LC-MS showed that the relative concentrations of most of the identified metabolites were higher in seedlings or juveniles than in adults. On the other hand, GC-MS analysis showed that methyl palmitate and methyl stearate were the most abundant in the early growth stages, whereas allantoic acid and palmitic acid prevailed as the plant matured. In summary, this is the first metabolomicscentered mining of U. sagittifolia compositional diversity focusing on chemical-level variability. These valuable findings offer a temporal view of metabolic changes during plant growth stages, which is useful for future bioprospecting, biological screening, and purification of metabolite-based therapeutics.